HEPATOPROTECTIVE EFFECT OF DRINK CONTAINING LACTOBACILLUS CASEI SHIROTA STRAIN IN FEMALE WISTAR RATS INDUCED BY PARACETAMOL - Tannusawiejaya, Marshalline
The use of paracetamol that is not following the recommended dose can cause liver damage. Lactobacillus casei Shirota stain (LcS) is probiotic, one of the nutritional supplements, that can improve liver function in patients with alcoholic liver cirrhosis. This study aimed to examine the hepatoprotective activity of Yakult® which contains Lactobacillus casei Shirota strain in female Wistar rats induced by paracetamol. This study was initiated by making animal models with liver damage through oral administration of paracetamol suspension, followed by hepatoprotective examination and their antioxidant effects. Three doses of LcS were tested that are doses equivalent to the use of 1 (D1), 2 (D2), and 3 (D3) bottles of Yakult® . The results showed that the three doses of LcS tested could significantly inhibit liver damage (p<0.01) which was indicated by lower ALT activity compared to controls with D1, D2, D3 vs control respectively (46.4±4.84 U/L, 52.14±7 U/L, 58±7.5 U/L vs 137.72±10.08 U/L) and AST (110.66±11.16 U/L, 81.86±9.61 U/L, 87.66±4.92 U/L vs 181.85±16.74 U/L). LcS doses of D2 and D3 could significantly improve liver function (p<0.05) as seen from albumin levels (3±0.29 g/dL, 3.03±0.2 g/dL vs 2.27±0.28 g/dL) and total protein (6.9±0.24 g/dL, 7.52±0.54 g/dL vs 5.27±0.56 g/dL). In the hepatoprotective mechanism test, the three doses of LcS could inhibit lipid peroxidation with MDA levels (4.13±0.31 µmol/g, 4.24±0.58 µmol/g, 3.8±0.29 µmol/g vs 7.82±0.43 µmol/g) and NO levels (39.4±1.57 µmol/L, 37.2±2.13 µmol/L, 35.75±1.44 µmol/L vs 54.6±0.69 µmol/L) significantly (p<0.01). The results of liver tissue examination showed that the three doses of LcS could repair the damage to hepatocytes. Based on the results of this study, LcS has benefits as a hepatoprotective in using paracetamol.